Parents in Neonatal Pain Management—An International Survey of Parent-Delivered Interventions and Parental Pain Assessment - Ullsten, Alexandra; Beken, Serdar; Campbell-Yeo, Marsha; Cavallaro, Giacomo; Decembrino, Nunzia; Durrmeyer, Xavier; Garrido, Felipe; Kristjánsdóttir, Guðrún; Amponsah, Abigail; Lago, Paola; Haslund-Thomsen, Helle; Ojha, Shalini; et al. (MDPI AG, 2025)
Background: While parent-delivered pain management has been demonstrated to effectively reduce neonatal procedural pain responses, little is known about to what extent it is utilized. Our aim was to explore the utilization of parents in neonatal pain management and investigate whether local guidelines promote parent-delivered interventions.
Methods: A web-based survey was distributed to neonatal units worldwide.
Results: The majority of the 303 responding neonatal intensive care units (NICUs) from 44 countries were situated in high-income countries from Europe and Central Asia. Of the responding units, 67% had local guidelines about neonatal pain management, and of these, 40% answered that parental involvement was recommended, 27% answered that the role of parents in pain management was mentioned as optional, and 32% responded that it was not mentioned in the guidelines. According to the free-text responses, parent-delivered interventions of skin-to-skin contact, breastfeeding, and parental live singing were the most frequently performed in the NICUs. Of the responding units, 65% answered that parents performed some form of pain management regularly or always.
Conclusions: There appears to be some practice uptake of parent-delivered pain management to reduce neonatal pain in high-income countries. Additional incorporation of these interventions into NICU pain guidelines is needed, as well as a better understanding of the use of parent-delivered pain management in low- and middle-income countries.